Financing SMEs and its effect on employment generation: a study of brae bank's SME lending - Rabbani, Mehnaz; Sulaiman, Munshi (BRAC, 2019)
Financial and development assistance designed specially for small and medium enterprises in Bangladesh is a new and upcoming trend. After the surge of micro-finance in the last two decades, small and medium enterprises have come to the limelight in the financial sector on account of their contribution to economy and yet limited access to finance. Both micro-finance institutions and banks are beginning to realize the potential of this market and designing new financial products for it. Brae Bank started providing credit to small and medium enterprises in 2002 in recognition of their special needs. This paper looks at the performance of small and medium enterprises that have received loans from Brae Bank with a focus on employment generation. The analysis reveals that employment generation is higher in enterprises with longer association with the Bank, enterprises in the manufacturing sectors and enterprises with a high initial labor force. Moreover, employment generated after repeat loans has a greater positive impact on the wage bill when compared to employment generated after first loans.